On exact constants in Jackson-type inequalities in the space L^2 - Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The exact dependence of constants in Jackson-type inequalities on the rate of convergence of the Diophantine approximations of certain numbers is obtained.